Regulation of citizenship in the territory of former SFR Yugoslavia - Dimitrijević Duško (Međunarodni Problemi)
The continuity with the former federal and republic nationality in the successor states of former SFRY confirms that it has kept on being regulated by their internal laws. However, not in all cases regulations of citizenship have been implemented in accordance with the provisions that are defined by international law. The basic nationality principles have not been applied to the citizens of different ethnic origin. For their own political interests the states did not take measures to duly grant citizenship to the persons that at the time of succession were nationals of the predecessor state. The delay in passing and implementing the laws, non-respect of the right of option, the exclusiveness of domestic citizenship and the absence of solutions for the protection of family unity had a negative reflection on the achievement of rights of citizens. The problems have gradually been overcome by introducing novelties in laws, by adopting administrative legislation and jurisprudence of the successor states, but as far as equality before the law is concerned some issues have remained unsolved.